КОНЦЕПТУАЛЬНІ ПІДХОДИ ДО МОДЕЛЮВАННЯ БЕЗПЕРЕРВНОЇ ЕКОЛОГІЧНОЇ ОСВІТИ (Педагогіка вищої та середньої школи, 2007)
The system of continuous ecological éducation is one the most important directions in the éducation of XXI century. It is directed to the development of students’ abilities, satisfaction of their interests and need in a professional détermination and growing.